Histopathology and Cytogenetics study in aborted women (Journal of the College of Basic Education, 2023)
This study has been made to draw attention to some causes of abortion. One hundred forms were filled for women with unknown cause of abortion. These forms are compared to another fifty women with normal delivery. The forms included the following parameters : consanguinity degree, maternal age and reproductive health parameter as (spontaneous abortion, still birth, and infant mortality in age less than two years). Forty two women are selected randomly from aborted women. They were classified into two groups, the first group contained thirty three women who aborted during first trimester. While the second group included nine women aborted in the 2nd trimester. Comparison was made with ten women who had normal pregnancy and delivery. Blood samples were collected in period from December 2010 till June 2011 in hospitals of Baghdad .Cytogenetic analysis of aborted women blood were made: they included chromosomal abnormalities and mitotic index, hence chromosomal abnormalities are important factors that are linked with recurrent spontaneous abortion in more than 60% of aborted women, where the studies found that at least one of parents (in 2-4% of couples suffering from recurrent spontaneous abortion) had special type of chromosomal abnormalities.Genetic study has reached the following results:-Absence of numerical and structural chromosomal abnormalities in blood samples of aborted women.Decline in mitotic index in blood samples of aborted women during 1st and 2nd trimaster of pregnancy in comparison with controlled group.presence of positive correlation between the total percentage of spontaneous abortion with maternal age and consanguinity degree in aborted women and control group (p <0.05).